2013
DOI: 10.3109/10641963.2013.776571
|View full text |Cite
|
Sign up to set email alerts
|

Change of Pulsatility Index of the Fetal Middle Cerebral Artery after Auditory Stimulation in No Risk Pregnancies and in Pregnancies with Gestational Hypertension

Abstract: An average change of PI of median cerebral artery was higher in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Several research groups have already demonstrated the link between fetal evoked responses to auditory stimuli and conditions during labor (Eswaran et al, 1999;Luz, 1985;Luz, Lima, Luz, & Feldens, 1980). In a large group of subjects, increase in fetal MCA flow was associated with gestational hypertension when compared to normotension (Plesinac et al, 2013). The objective of the present study was to establish whether there is a potential correlation between antenatal maternal anxiety and changes in blood flow in the fetal MCA in normotensive and gestational hypertensive subjects and if maternal anxiety acts additively with gestational hypertension.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Several research groups have already demonstrated the link between fetal evoked responses to auditory stimuli and conditions during labor (Eswaran et al, 1999;Luz, 1985;Luz, Lima, Luz, & Feldens, 1980). In a large group of subjects, increase in fetal MCA flow was associated with gestational hypertension when compared to normotension (Plesinac et al, 2013). The objective of the present study was to establish whether there is a potential correlation between antenatal maternal anxiety and changes in blood flow in the fetal MCA in normotensive and gestational hypertensive subjects and if maternal anxiety acts additively with gestational hypertension.…”
Section: Discussionmentioning
confidence: 86%
“…PAS was performed essentially following the protocol of Sovilj et al (1992) as previously described (Dobrijević et al, 2009; Jankovic-Raznatovic et al, 2014; Plesinac et al, 2013). Standard ultrasound examination was employed to determine that fetuses were in proper health and awakemoving limbs, yawning, blinking, etc.…”
Section: Prenatal Acoustic Screening (Pas) and Doppler Sonographymentioning
confidence: 99%
See 3 more Smart Citations